Ontological (In)Security - Art Students’ Experience of Agency in the Educational Reality During the Pandemic - Agnieszka Weiner (Multidisciplinary Journal of School Education, 2023)
Objectives of the study: The purpose of the study is to reconstruct the experiences of art students during the Covid-19 pandemic. The research question is as follows: What image of the everyday life of remote education emerges from the reconstruction of the experiences of students who were previously assigned to extreme groups in terms of their perceived proficiency?